2021
DOI: 10.3390/v13061140
|View full text |Cite
|
Sign up to set email alerts
|

Global mRNA and miRNA Analysis Reveal Key Processes in the Initial Response to Infection with WSSV in the Pacific Whiteleg Shrimp

Abstract: White Spot Disease (WSD) presents a major barrier to penaeid shrimp production. Mechanisms underlying White Spot Syndrome Virus (WSSV) susceptibility in penaeids are poorly understood due to limited information related to early infection. We investigated mRNA and miRNA transcription in Penaeus vannamei over 36 h following infection. Over this time course, 6192 transcripts and 27 miRNAs were differentially expressed—with limited differential expression from 3–12 h post injection (hpi) and a more significant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 121 publications
(152 reference statements)
0
10
1
Order By: Relevance
“…The average proportion of sequences that were WSSV-derived in these six crabs was 4.7% (± 2.9, one standard deviation). In contrast, viral transcripts in highly susceptible P. vannamei were first observed at 3 h and increased from 0.3% to approximately 40% of expressed transcripts in the first 24h following infection ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average proportion of sequences that were WSSV-derived in these six crabs was 4.7% (± 2.9, one standard deviation). In contrast, viral transcripts in highly susceptible P. vannamei were first observed at 3 h and increased from 0.3% to approximately 40% of expressed transcripts in the first 24h following infection ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…These groups were injected with either saline solution or WSSV-infected shrimp homogenate for the disease trial and the gills of 8 crabs were sampled from saline and WSSV-injected treatment groups at 0, 6, 12, 24, 48, 168, 336 and 672 hours and snap frozen for transcriptome sequencing. The lower panel illustrates the equivalent time course experiment in the susceptible shrimp ( P. vannamei ) reported in a previously published WSSV-exposure dataset utilised for comparison ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…japonicus 49 and Pacific oysters Crassostrea gigas , 50 indicating that viruses can exploit VDAC. Recently, Millard et al revealed that in addition to cytoskeleton remodelling and changes in phagocytic activity that aids entry and translocation of WSSV, miRNA‐induced metabolic shifts also occur, indicating that miRNA‐induced metabolites participate in host–viral interactions 51 …”
Section: Changes In Host Metabolomementioning
confidence: 99%